The relationship between main stressors and occupational stress among the government primary school administrators in Kuching - Valentina, Edwin (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study aims to investigate the relationship between main stressors and occupational stress among the government primary school administrators. This study was conducted in primary schools in the Kuching area. The statistical analysis showed that surprisingly, none of the demographic characteristics of the respondents were significantly different with regard to the occupational stress while at the same time I was discovered that stressors intrinsic to actual job, stressors related to role in the organization as well as stressors related to organizational structure and climate had significant relationship with occupational stress.